ESTABLISH EFFECTIVE USE OF AVAILABLE FINANCIAL RESOURCES OF COMMERCIAL BANKS - Ahmad Eshkobilov Javlievich (Galaxy International Interdisciplinary Research Journal, 2023)
This article explores the importance of effectively utilizing the existing financial resources of commercial banks and proposes strategies for optimal resource management. By examining the methods, results, and discussions, we aim to provide insights into how commercial banks can maximize the use of their financial resources to enhance profitability, mitigate risks, and support sustainable growth.